A Method for the Computational Representation of Croatian Morphology - Štefanec, Vanja (Array, 2013)
In this paper we present the development of the Croatian Derivational Database (CroDeriV), a unique language resource for the Croatian language. We describe the initial stage of its development as well as its redesign according to insight gained from data analyzed thus far. We believe that the data model we have presented will enable us to encode all derivational processes in Croatian. We also believe that our model is sufficiently flexible and abstract that it could be used for other morphologically “rich” languages.